Quantitative Structure-Activity Relationship Study on Pyrrolotriazine Derivatives as Met Kinase Inhibitors - Sharma, B.K.; yashwant; Srivastava, B. (Asian Journal of Chemistry, 2010)
Met kinase inhibitory activity of pyrrolotriazine derivatives has been quantitatively analyzed in terms of Dragon descriptors using combinatorial protocol in multiple linear regression (CPMLR). The study has provided a rational approach for the development of new pyrrolotriazine derivatives as Met kinase inhibitors. The descriptors identified in CP-MLR analysis have highlighted the role of atomic Sanderson's electronegativity in modified Burden eigen value (BELe4) and in respective lag of 2D-autocorrelation (GATS7e), 9th order self-returning walk count (SRW09), structural information content of 4th order neighbourhood symmetry (SIC4) and aromatic ratio (ARR) to explain the Met kinase inhibitory activity of pyrrolotriazine derivatives. Certain structural fragments (C-005 and N-069) and number of five membered rings (nR05) in molecular structures have also shown prevalence to optimize the Met kinase inhibitory activity of pyrrolotriazine derivatives. These guidelines may be used to develop new Met kinase inhibitors based on pyrrolotriazine scaffold.